The Tenderness of God : Reclaiming Our Humanity - Ahlgren, Gillian T. W. (Book collections on Project MUSE., 2017)
At moments in history, individuals have embodied the gospel message with creativity and passion. Capitalizing on the legacy of Francis and Clare and the new energy of a visionary pope who raises critical questions about how to be faithful to the gospel, The Tenderness of God invites readers into a rich conversation across time and space about how to recapture our humanity and nurture our God-given capacity to live meaningfully and joyfully in communion with others.